Valoriser les produits du palmier doum pour gérer durablement le système agroforestier d’une vallée sahélienne du Niger et éviter sa désertification - Régis Peltier; Claudine Serre Duhem; Aboubacar Ichaou (VertigO)
In the Mayahi region, south-centre of Niger, the inventory of woody species occurring in a valley has been completed. Studies have also been carried out on chains marketing products harvested on these woody species. A small-sized palm-tree, the doum, has proved to have a significant economic, social and ecological value.The wood of its stem, mechanically resistant and little damaged by termites, is used as timber. The pulp of its fruit is eaten, dried palm cores produce edible flour, several parts are used as fuel, palm-trees have a favorable influence on associated crops or pastures… and above all the limb of young leaves is used for numerous craft products (ropes, mats, etc.). Thanks to a very active chain, this meets local populations’ needs and provides financial incomes which are indispensable for the survival of the poorest. The general degradation of the Sahelian environment and his desertification, on account of climate uncertainties and increase of anthropic pressure, allows to fear an overexploitation of the doum palm-tree which would lead to the disappearance of adult seed trees, then to sprout exhaustion and disappearance of young seedlings. This phenomenon could be worsened by the ongoing drying out of the valley due to dam construction upstream in Nigeria. Farmers’ experience shows that it is possible to let a sprout develop a stem which grows relatively rapidly, provided it is not cut for several years. In areas where the doum is associated with crops, a mere dissemination of the Assisted Natural Regeneration (ANR) technique among the population can allow farmers to restore a sustainable agroforestry park of adult palm-trees. In sylvo-pastoral areas, where the space and plants are not private property, it will be more difficult. Also, the chain organization was tested through a leaf market. It is still too early to know if this will bring sustainable improvement to chain functioning, threatened by imported products. The ideal would be to have new chains (fair international trade) giving value to craft products and inciting populations to sustainably manage Sahelian doum groves.